2021
DOI: 10.1126/sciadv.abf4213
|View full text |Cite
|
Sign up to set email alerts
|

Probing the photointermediates of light-driven sodium ion pump KR2 by DNP-enhanced solid-state NMR

Abstract: The functional mechanism of the light-driven sodium pump Krokinobacter eikastus rhodopsin 2 (KR2) raises fundamental questions since the transfer of cations must differ from the better-known principles of rhodopsin-based proton pumps. Addressing these questions must involve a better understanding of its photointermediates. Here, dynamic nuclear polarization–enhanced solid-state nuclear magnetic resonance spectroscopy on cryo-trapped photointermediates shows that the K-state with 13-cis retinal directly interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 73 publications
3
30
0
Order By: Relevance
“…For WT9 , however, an additional but slightly delayed lifetime component is found in the spectral range of 330–360 nm. This component, in turn, correlates well with the lifetime found for the formation of the O intermediate, being indicative for the reisomerization process from 13- cis to all- trans , as shown in Jakdetchai et al and Kovalev et al , These findings suggest that the near-UV signature is in fact a composition of two overlapping features. The first contribution is centered around 335 nm and spans from the femtosecond time scale up to the late steps of the photocycle and can therefore be considered as a marker band for the 13- cis isomer of retinal.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…For WT9 , however, an additional but slightly delayed lifetime component is found in the spectral range of 330–360 nm. This component, in turn, correlates well with the lifetime found for the formation of the O intermediate, being indicative for the reisomerization process from 13- cis to all- trans , as shown in Jakdetchai et al and Kovalev et al , These findings suggest that the near-UV signature is in fact a composition of two overlapping features. The first contribution is centered around 335 nm and spans from the femtosecond time scale up to the late steps of the photocycle and can therefore be considered as a marker band for the 13- cis isomer of retinal.…”
supporting
confidence: 82%
“…Whereas the structures by Skopintsev et al and Kato et al were reported to be monomers, the structure of Kovalev et al was reported as a pentamer. In contrast to the compact monomer, the more expanded conformation in the KR2 pentamer contains a large water cluster in the retinal binding pocket. ,, This could affect the spectral properties of retinal itself and in turn partly account for the deviations of the calculated energies with respect to the experiment.…”
mentioning
confidence: 99%
“…and ability to shed its hydration shell. In fact, while bacteriorhodopsin is a light-driven proton pump (Wickstrand et al, 2019), some bacteriorhodopsins pump sodium cations (Jakdetchai et al, 2021), and others chloride anions (Schobert and Lanyi, 1982). Similarly, while most F-type and V-type ATPases pump protons, some pump sodium cations (Mulkidjanian et al, 2008).…”
Section: Proton Transfer and Mobility In Proteinsmentioning
confidence: 99%
“…Dead times can be as short as 50 ms nowadays (Mok et al, 2003;Schlepckow et al, 2008). A further extension of time-resolved NMR is to utilise freeze quenching as an approach that couples rapid induction of biomolecular folding with rapid freezing of the acquired conformational ensemble at appropriate time points after folding induction to study its properties by solid-state NMR spectroscopy (Etzkorn et al, 2007;Jeon et al, 2019).…”
Section: Techniques To Trigger Real-time Nmr Experimentsmentioning
confidence: 99%
“…The first attempts, initially without the help of DNP, date back to 1994 (Ramilo et al, 1994). Recently, remarkable progress has been achieved by combining rapid mixing and freeze quenching with DNP by which a time resolution in the millisecond range could be achieved (Jeon et al, 2019). Another possibility is cryotrapping of lightinduced photoreceptor intermediates under DNP conditions, which is briefly addressed below.…”
Section: Dnpmentioning
confidence: 99%